Effects of inorganic nitrate and beetroot supplementation on endothelial function: a systematic review and meta-analysis - Lara, Jose; Ashor, Ammar W; Oggioni, C; Ahluwalia, A; Mathers, John C; Siervo, Mario (European journal of nutrition, 2016)
BACKGROUND: Diets rich in inorganic nitrate are associated with lower blood pressure, an effect that may be mediated by an improvement of endothelial function (EF). Therefore, a systematic review and meta-analysis of randomised controlled trials (RCTs) were conducted to examine the effects of inorganic nitrate and beetroot supplementation on measures of EF. METHODS: MEDLINE, EMBASE and Scopus databases were searched from inception until November 2014. Specific inclusion criteria were as follows: (1) RCTs; (2) trials comparing inorganic nitrate or beetroot supplementation with placebo control groups; and (3) trials reporting effects of these interventions on outcomes of vascular function. Random-effect models were used to assess the pooled effect sizes showed as standardised mean differences (SMD). RESULTS: Nine crossover trials and three parallel trials met our inclusion criteria. The trials were conducted between 2008 and 2014 and included a total of 246 participants with 10–64 participants per study. The duration of each intervention ranged from 1.5 h to 28 days. Inorganic nitrate and beetroot consumption was associated with an improvement in vascular function (SMD 0.36; 95 % CI 0.16, 0.56; P < 0.001). The effect on EF was significantly associated with the dose of inorganic nitrate (β = 0.04, SE = 0.01, P < 0.001), age (β = −0.01, SE = 0.004, P = 0.02), baseline BMI (β = −0.04, SE = 0.02, P = 0.05) and systolic BP (β = −0.01, SE = 0.005, P = 0.02). CONCLUSIONS: Inorganic nitrate and beetroot supplementation was associated with beneficial effects on EF. These effects appear to be reduced in older subjects and in subjects with greater cardiometabolic risk.